CYBER RISK MITIGATION IN CLOUD COMPUTING ENVIRONMENTS USING BLOCKCHAIN TECHNOLOGY - Harsh Sengar , Sujata Joshi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Cloud Computing has gained widespread use over the past few years. However, in recent times, there is an alarming rise in the cyber-crimes across the globe which has made it a major concern. IT systems and the information generated is being target of the advanced cyber-attacks therefore threats to data integrity are of foremost pertinence. Blockchain technology is providing convincing properties about data integrity. In academic research, very few studies have focused on how Blockchain Technology can be used in cloud computing environments for data integrity. The objective of this paper is to comprehend how Blockchain can be used to mitigate the data integrity threats caused due to various cyber-attacks in the cloud computing environment. Case study approach has been adopted for this study wherein the use cases of Blockchain Technology in cloud computing environments are briefly discussed along-with future applications which will help create customized solutions for the clients.